1983
DOI: 10.1103/physrevlett.50.768
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multielectron Excitations on the Band Structure of Adsorbate Overlayers

Abstract: Photoelectron spectra from ordered CO on Cu(lll) exhibit anomalously small 4<7 band dispersion compared to all other CO adsorption systems previously studied. The bonding 5a band displays normal one-electron dispersion. It is shown that the energy dependence of the 4cr band expected for a single-particle system is transferred into fe-dependent intensity variations of the quasiparticle excitation and the intense satellite line ^2 eV lower in energy. The first moment of the spectral weight function over this ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…In the presence of strong electron correlation effects, the photoemission spectral function is observed, where the peak positions do not immediately reflect the ground state calculated bands anymore. This had been theoretically formulated by Hedin and Lundquist (34,35) and was quantitatively confirmed by studying the fairly simple band structure of an ordered CO adsorbate layer (36). This however means that now the relative peak intensities and line shapes have to be used in the interpretation, rather than the simple peak positions.…”
Section: Introductionmentioning
confidence: 88%
“…In the presence of strong electron correlation effects, the photoemission spectral function is observed, where the peak positions do not immediately reflect the ground state calculated bands anymore. This had been theoretically formulated by Hedin and Lundquist (34,35) and was quantitatively confirmed by studying the fairly simple band structure of an ordered CO adsorbate layer (36). This however means that now the relative peak intensities and line shapes have to be used in the interpretation, rather than the simple peak positions.…”
Section: Introductionmentioning
confidence: 88%
“…Since initial and final states are expanded in different sets of one particle functions it is not possible to discuss satellites directly in the way we did in connection with Eq. (9). Certainly, projection techniques can be applied to overcome this drawback, but it is much easier for this purpose to use some of the direct methods.…”
Section: Indirect Methodsmentioning
confidence: 98%
“…Manne and Aberg [8] have shown that in cases where the satellites derive their intensity exclusively from one main line, as it usually happens for core ionizations, the orbital energy can be obtained from the intensity weighted average of the energy of the main line and all satellites including the continuum. The latter is an important limitation for the experimental applicability of the ManneAberg theorem [9]. Sometimes the expansion of 1 9 Y -l ) is dominated by a specific 2hlp state.…”
Section: Some Basic Definitionsmentioning
confidence: 98%
“…Photoelectron spectroscopy (PES) is a very sensitive tool with which to monitor the change in the electronic structure, which is why it is the method of choice to shed light on this question [130]. There are several interesting differences in binding energies, line intensities and line shapes between gas phase [134], condensed phase [135] and adsorbate phases [132,133,[136][137][138][139], which we shall comment on in the following. For comparison, we show the spectrum of gaseous [134] and condensed CO [135].…”
Section: Structure Sensitivitymentioning
confidence: 99%
“…Figure 20 shows a set of photoelectron spectra of CO adsorbates on four different hexagonally close packed metal surfaces [131], as well as on two transition metal-oxide surfaces [132,133]. We shall start with the adsorbates on the metal surfaces [136][137][138][139], and later turn to the oxide surfaces [132,133] because bonding considerations are rather different for these systems. The binding energy (E b = E kin − hv) refers to the vacuum level, which allows us to place adsorbates on metals, on insulators, and molecular solids on the same energy scale.…”
Section: Structure Sensitivitymentioning
confidence: 99%